Reconstruction of Furniture Production as Potential and Reputable Intellectual Property Rights (IPR) Creative Design Model - husen hendriyana (Mudra Jurnal Seni Budaya, 2017)
Along with recent rapid development of science, technology, art and culture, through research institutions from the central to the local level, the government seriously activates enhancement and protection of the intellectual products of the nation. Such as protection of intellectual property rights against irresponsible plagiarism. This is due to that the appearance, process, or invention steps of the creative furniture designer in the society or in the academic environment have the potential and the opportunity to be registered as Intellectual Properties (IP) or gain Intellectual Property Rights (IPR). Besides aiming to lift up the state or institutions achievement and attainment of intellectual property rights internationally, the added value also can be developed in the direction of economic upgrade. Research on furniture products designs have been numerously carried out with various objects and cases, yet the diversity of the subject character and creative processes still have not well defined so they enrich the model of creative process design. This study aims to identify, classify and formulate a potential furniture design model of creative process and IPR standard, through methods PAR. The results of this study are (1) prototype of furniture design products, (2) the creative process model and the construction methods process of furniture design with a concept or a specific theme; (3) Registration of IPR; (4) Scientific manuscript.Seiring dengan perkembangan ilmu pengetahuan, teknologi, seni dan budaya yang marak dewasa ini, melalui lembaga penelitian dari tingkat pusat sampai ketingkat daerah, pemerintah semakin serius menggalangkan peningkatan dan perlindungan terhadap produk intelektual anak bangsa. Salah satu contoh di antaranya adalah perlindungan terhadap hak kekayaan intelektual dari perilaku plagiarism yang tidak bertanggung jawab. Hal ini tiada lain bahwa, bentuk, proses, maupun invention steps dari para pelaku kreatif desain mebel yang ada di masyarakat maupun di lingkungan akademik memiliki potensi dan peluang untuk didaftarkan sebagai Intellectual Properties (IP) atau Hak Kekayaan Intelektual (HKI). Selain bertujuan mendongkrak prestasi lembaga maupun Negara dalam perolehan HKI di kancah Internasional, juga pada nilai tambah dapat dikembangkan ke arah peningkatan ekonomi. Penelitian desain produk mebel telah banyak dilakukan orang dengan berbagai objek dan kasusnya, tetapi keragaman karakter dan proses kreatif yang ada belum banyak didefinisikan dengan baik untuk memperkaya model proses kreatif desain. Penelitian ini bertujuan untuk mengidentifikasi, mengklasifikasi dan merumuskan model proses kreatif desain mebel yang berpotensi dan bereputasi HKI dengan metode PAR. Hasil penelitian ini berupa (1) prototype produk desain mebel, (2) model proses kreatif dan metode proses perancangan desain mebel dengan konsep atau tema tertentu; (3) Pendaftaran HKI; (4) Naskah Ilmiah.